Exploring usability metrics in continuous glucose monitoring systems: insights from the voice of people with diabetes in Italy - Manzoni, Martina; Minotti, Davide; Toletti, Giovanni; Boaretto, Andrea (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionContinuous Glucose Monitoring (CGM) systems are crucial in diabetes management, offering clinical and psychological benefits despite operational challenges. Usability assessment of real-time and intermittently-scanned CGM systems is a notable research gap. This study, in collaboration with diabetes patient associations, explores CGM usability from the perspective of Italian individuals with diabetes.MethodsA roundtable discussion with patient association representatives was conducted to discuss CGM usability, followed by a detailed online survey of 281 Italian patients on CGM usage, satisfaction, and feature preferences.ResultsFindings show a significant positive impact on Quality of Life (87/100) and moderate usability (66/100). Core CGM functions are widely used, while data sharing with healthcare professionals is underutilized. The study offers diverse insights into CGM usability from both the roundtable and survey data.ConclusionsThe study underscores the importance of CGM in diabetes management and highlights the need for continuous technological improvements. It emphasizes the role of patient associations in enhancing communication with manufacturers and CGM education. Effective collaboration between healthcare professionals and patients is vital for optimal CGM use, advocating for personalized care strategies tailored to individual patient needs.